Exploring clinical reasoning development perspectives among final year medical students - Gul Mehar Javaid Bukhari; Abel Jacobus Pienaar; Gideon Victor; Sara Khan; Javeria Saleem (Educación Médica)
Introduction: Clinical reasoning is essential for effective clinical practice. Clinical reasoning helps medical students for clinical decision-making. However, development of clinical reasoning is challenging. The purpose of this study was to explore clinical reasoning perspectives among final year medical students. Methods: Exploratory descriptive qualitative research design was employed. The study was approved by the Institutional Review Board and Ethics Committee. Data were collected through focused group discussion from 2 medical colleges in English language. A semi-structured guide was used for data collection. Manual content analysis was applied for data analysis. The data were summarized in categories, subcategories that were presented with their pertinent direct quotes. Results: Six categories namely mentoring support and guidance, learning challenges, teaching and learning methods, assessment and feedback, systematic thinking, and being a life-long learning were developed. The categories represented appreciating and devaluating expressions of medical students for the development of clinical reasoning. Medical students expressed the need for mentoring, bridging theory-practice gap, clinical resources, thinking systematically and role of life-long learning. Whereas, curriculum overload, decontextualized curriculum, practice inconsistencies, and cultural issues hinder development of clinical reasoning. Challenges can be alleviated with effective clinical strategies, role modeling, being and becoming life-long learner and evidence-based medical practices. Conclusion: Medical students were aware about the significance of clinical reasoning. However, development of clinical reasoning was hinder by number of learning challenges. Alleviation of learning challenges is imperative for the development of clinical reasoning. Resumen: Introducción: El razonamiento clínico es esencial para una práctica clínica efectiva. El razonamiento clínico ayuda a los estudiantes de medicina en la toma de decisiones clínicas. Sin embargo, el desarrollo del razonamiento clínico es un desafío. El propósito de este estudio fue explorar las perspectivas del razonamiento clínico entre los estudiantes de medicina de último año. Métodos: Se utilizó un diseño de investigación cualitativa descriptiva exploratoria. El estudio fue aprobado por la Junta de Revisión Institucional y el Comité de Ética. Los datos fueron recopilados a través de discusiones de grupo focal en dos colegios de medicina en idioma inglés. Se empleó una guía semiestructurada para la recopilación de datos. Se aplicó un análisis de contenido manual para el análisis de datos. Los datos se resumieron en categorías y subcategorías que se presentaron con sus citas directas pertinentes. Resultados: Se desarrollaron seis categorías, a saber: apoyo y orientación de mentoría, desafíos de aprendizaje, métodos de enseñanza y aprendizaje, evaluación y retroalimentación, pensamiento sistemático y aprendizaje a lo largo de la vida. Las categorías representaron expresiones de aprecio y devaluación de los estudiantes de medicina para el desarrollo del razonamiento clínico. Los estudiantes de medicina expresaron la necesidad de mentoría, la superación de la brecha entre la teoría y la práctica, recursos clínicos, pensamiento sistemático y el papel del aprendizaje continuo. Mientras tanto, la sobrecarga de currículo, el currículo descontextualizado, las inconsistencias en la práctica y los problemas culturales obstaculizan el desarrollo del razonamiento clínico. Los desafíos pueden ser aliviados con estrategias clínicas efectivas, modelado de roles, ser y convertirse en aprendiz de por vida y prácticas médicas basadas en evidencia. Conclusión: Los estudiantes de medicina eran conscientes de la importancia del razonamiento clínico. Sin embargo, el desarrollo del razonamiento clínico se vio obstaculizado por una serie de desafíos de aprendizaje. La mitigación de estos desafíos de aprendizaje es imperativa para el desarrollo del razonamiento clínico.